ELECTRICAL LOAD RELIABILITY ASSESSMENT USING ANALYTICAL METHOD, CASE STUDY: FUPRE 1 X 2.5MVA INJECTION SUBSTATION - AMAKIRI OKILO FRIDAY; OSHEVIRE PATRICK (Journal of Engineering Studies and Research, 2020)
This research work presents the reliability assessment of electrical load distribution system in Federal University of Petroleum Resources, Effurun (FUPRE), Warri using the Analytical method and ETAP software as the simulation tool to run the reliability assessment of the System. The analytical analysis was conceded out by using August 2018 – August 2019 historical data of Tetfund Classrooms Blocks, Hostels, College of Technology, Administration Block, Health Center, and College of Science Feeder obtained from the Benin Electricity Distribution Company [BEDC]. The results conceded revealed that College of Technology Injection Substation is the most reliable in the distribution network when compared to the other five substations around the institution premises as it recorded system indices of ASAI: 99.30, SAIFI: 1.10, SAIDI: 55.35, CAIDI: 123.04 in August 2018 to August 2019. Nevertheless, the total reliability indices of the six substations under investigation as obtained from the analysis, and it shows that availability of power to FUPRE distribution is very poor as compared with the benchmark of IEEE ASAI of 99.99 for distribution substation availability.